2016
DOI: 10.3390/polym8020042
|View full text |Cite
|
Sign up to set email alerts
|

Application of Collagen Scaffold in Tissue Engineering: Recent Advances and New Perspectives

Abstract: Abstract:Collagen is the main structural protein of most hard and soft tissues in animals and the human body, which plays an important role in maintaining the biological and structural integrity of the extracellular matrix (ECM) and provides physical support to tissues. Collagen can be extracted and purified from a variety of sources and offers low immunogenicity, a porous structure, good permeability, biocompatibility and biodegradability. Collagen scaffolds have been widely used in tissue engineering due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
416
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(430 citation statements)
references
References 132 publications
0
416
0
14
Order By: Relevance
“…[16][17][18] Moreover, collagen, as the organic constituent of the bone extracellular matrix, is a promising biomaterial owing to its excellent biocompatibility, cell affinity and biodegradability. [19][20][21] Consequently, the HAP/ collagen (HAP/Col) composite scaffolds can chemically and structurally mimic the natural bone, and have excellent bioactivity, biodegradability and osteoinductive activity. 11,13,22 So far, the biomimetic HAP/Col composite scaffolds with high porosity are typically fabricated via lyophilisation, which is benecial for cell inltration, neovascularization and new bone ingrowth.…”
Section: -10mentioning
confidence: 99%
“…[16][17][18] Moreover, collagen, as the organic constituent of the bone extracellular matrix, is a promising biomaterial owing to its excellent biocompatibility, cell affinity and biodegradability. [19][20][21] Consequently, the HAP/ collagen (HAP/Col) composite scaffolds can chemically and structurally mimic the natural bone, and have excellent bioactivity, biodegradability and osteoinductive activity. 11,13,22 So far, the biomimetic HAP/Col composite scaffolds with high porosity are typically fabricated via lyophilisation, which is benecial for cell inltration, neovascularization and new bone ingrowth.…”
Section: -10mentioning
confidence: 99%
“…Using collagen for tissue engineering applications has many merits such as biocompatibility, biodegradability, suitable permeability and low immunogenicity. Conversely, it is found that collagen suffers from poor mechanical properties …”
Section: Injectable Hydrogels In Myocardial Tissue Engineeringmentioning
confidence: 99%
“…Without considerable crosslinking, type-I collagen has relatively weak mechanical properties and is difficult to handle or fabricate compared to competing synthetic or modified polymers 17 . Type-I collagen forms highly ordered D-banded fibers at physiological conditions that are vital for the natural presentation of bioactive epitopes and for providing anisotropic strength and stiffness, and it requires high concentrations or crosslinking to match properties of tissues 18,19 . These properties can significantly complicate 3D printing when using collagen as bio-ink, especially forms of nozzle-based 3D printing 1821 .…”
Section: Introductionmentioning
confidence: 99%
“…Type-I collagen forms highly ordered D-banded fibers at physiological conditions that are vital for the natural presentation of bioactive epitopes and for providing anisotropic strength and stiffness, and it requires high concentrations or crosslinking to match properties of tissues 18,19 . These properties can significantly complicate 3D printing when using collagen as bio-ink, especially forms of nozzle-based 3D printing 1821 . Alternatively, type-I collagen can be cast in specific geometries, but this requires the use of a negative mold to construct the tissue of interest 3,4,22 , which can delay treatment for the patient due to increased processing times for scaffold customization, a major benefit of 3D printing.…”
Section: Introductionmentioning
confidence: 99%